Horizontal and Vertical Handheld Pointing Devices Comparison for Increasing Human Systems Integration at the Design Stage - Lourenço, Miguel (2017)
In addition to postural and biomechanical aspects related to usage of handheld pointing devices it is also important to perform usability assessment. The paper reports on an experimental study comparing two computer pointing devices, a standard horizontal PC mouse and a vertical device (for neutral pronation of the forearm), both commercially available. The standardized tasks implemented by software and performed by 20 experienced computer mouse users included pointing, dragging and steering. The usability parameters of effectiveness and efficiency were calculated and the participants subjectively assessed their discomfort, effort and ease of use in relation to each device in each task. Efficiency and effectiveness were higher for the horizontal device. Assessments of discomfort, effort and ease of use across the different tasks also supported the consideration of preference for the horizontal device in detriment of the vertical model. The results suggest that designing hybrid configurations may configure a better compromise.